english: english - Ahnaf Alaudin Bayu Pratama (CV. AFDIFAL MAJU BERKAH, 2026)
This study analyzes the interpretation of registered trademark use in trademark cancellation practices in Indonesia from a legal certainty perspective. It aims to assess the extent to which the regulations and their implementation provide predictable and consistent legal certainty for trademark owners and interested third parties. The research employs a normative legal approach, examining relevant laws, regulations, and expert opinions. It identifies a normative gap in Indonesian trademark law regarding the definition and criteria for trademark use, leading to legal uncertainty in cancellation proceedings. The absence of clear parameters for trademark use results in inconsistent interpretations and court decisions, potentially harming trademark owners, especially SMEs. The study concludes that a clear, objective, and proportional standard for trademark use is necessary to ensure fair and balanced legal certainty in trademark cancellation practices in Indonesia. This standard should consider the function of trademarks as distinguishing marks in commerce, business realities, and the characteristics and scale of businesses, including micro, small, and medium enterprises (MSMEs)